Las plataformas Streaming en las preferencias del nuevo consumidor universitario, Universidad Particular Antenor Orrego y Universidad Nacional de Trujillo – 2016 - Carranza Narro, Annie Katherine (2019)
The present investigation, Streaming platforms in the preferences in the new university consumer, Antenor Orrego Particular University and National from Trujillo University - 2016, has as general objective to determine the preferences of the Streaming platforms by the new university consumer Antenor Orrego Particular University and National from Trujillo University. The investigation according to the design is non-experimental, descriptive, transversal, technological and propositive. The method that was used was deductive-inductive, analytical and synthetic. The sample consisted of 64 students; 28 from the Antenor Orrego Particular University and 36 from Trujillo’s National University. The survey technique was applied with the questionnaire instrument to gather information necessary for the development of this research. This investigation determined that there is a tendency in the new university consumer towards the use of free streaming platforms, due to its easy use, availability and extensive catalog; such is the case of YouTube, which is why a proposal is proposed for the use of it as a learning support tool for the new university consumer.